Validation of a multiplexed LC–MS/MS clinical assay to quantify insulin-like growth factor-binding proteins in human serum and its application in a clinical study - Liu, Nanjun; Tengstrand, Elizabeth; Boernsen, K. Olaf; Bek, Stephan; Hsieh, Frank (Toxicology and applied pharmacology, 2019)
Circulating insulin-like growth factor-binding proteins (IGFBPs) continue to gain attention as biomarkers of drug activities on insulin like growth factor (IGF)/IGF receptor signaling pathways. A multiplexed LC–MS/MS method was validated for the absolute quantitation of IGFBPs in human serum. The method was used to measure screening concentrations of IGFBPs in spinal and bulbar muscular atrophy (SBMA) patients in a phase 2 clinical trial. Concentrations of IGFBP 1, 2, 3, and 5 were simultaneously determined based on representative signature peptides derived from an optimized trypsin digestion procedure. Signature peptide levels were absolutely quantitated using a sensitive/specific targeted LC–MS/MS method. Corresponding mass-shifted, stable isotope-labeled peptides were employed as internal standards. A true blank matrix for the quantitation of IGFBPs was not available since they are endogenous proteins in human serum. In this method, calibration standards/curves were prepared using authentic synthetic peptides spiked into a surrogate matrix. The surrogate matrix was generated from human serum treated in the same way as the study samples, but using iodoacetic acid instead of iodoacetamide as the alkylation reagent. This surrogate matrix approach allowed for the direct and sensitive/specific quantification of IGFBP 1, 2, 3, and 5 due to the lack of any endogenous background. Equivalent matrix effect and recovery of analytes was achieved for the authentic and surrogate matrices. The fully validated LC–MS/MS assay will allow further evaluation of the utility of IGFBP biomarkers in clinical trials. [Display omitted] •GLP validated multiplex LC–MS/MS assay for efficacy protein biomarker quantitation.•Simultaneous monitoring of four IGFBPs (IGFBP1, 2, 3, and 5) in human serum•Surrogate matrix approach for sensitive/specific measurement of endogenous proteins•Measure concentrations of serum IGFBPs in subjects in a phase 2 clinical trial•Increase quality and throughput of protein biomarker analyses in clinical trials